GE_GERICHTE P/19228/2021 vom 23. November 2022 - GE Cour de justice (2022)
INFRACTIONS CONTRE LE DOMAINE SECRET;MENACE(DROIT PÉNAL);PLAINTE PÉNALE;DÉLAI;INFRACTIONS CONTRE L'HONNEUR;DÉPENS;PLAIGNANT | CPP.319; CP.179septies; CP.180; CP.31; CP.174; CP.173; CP.177; CPP.433.al1.letb